Advanced financial accounting - Lewis, Richard; Pendrill, David (London : Financial Times Management, 1996)
Provides a comprehensive treatment of current financial reporting in the UK and is the leading textbook for 2nd and 3rd year courses in universities. Basic and advanced questions are provided at the end of the book.
Includes bibliographical references and index.
oif 11/03/15
Loan
Keywords: Accounting